IMPACTS OF ACCOUNTING METHODS IN GENERAL CORPORATIONS: CRITICAL REVIEW - Kifah Sami Hussein (Scholars Digest Publishing, 2024)
Management accountants play a crucial role in advising top management and policymakers on financial matters to ensure the effective and efficient use of resources within an organization. The airline industry, both in the United States and globally, is characterized by intense competition, with a constant stream of new services and equipment innovations to meet evolving customer needs. Within airlines, management accountants are heavily involved in the budgeting process, which entails using historical and current data to make future financial decisions and plans. Budgeting is a vital financial management tool that helps ensure adherence to a business's operating policies and provides a framework for future operations. Additionally, management accountants in the airline industry analyze past and present performance to predict future operations, enabling companies to anticipate future needs and develop appropriate budgets.
Keywords: Accounting, accounting Methods, Air-company, Critical review.